2020
DOI: 10.1021/acs.jpcc.0c09747
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Silica/Divalent Electrolyte Interface: Molecular Insight into Charge Inversion with Increasing pH

Abstract: The molecular origin of overcharging at mineral oxide surfaces remains a cause of contention within the geochemistry, physics, and colloidal chemistry communities owing to competing "chemical" vs "physical" interpretations. Here, we combine vibrational sum frequency spectroscopy and streaming potential measurements to obtain molecular and macroscopic insights into the pH-dependent interactions of calcium ions with a fused silica surface. In 100 mM CaCl 2 electrolyte, we observe evidence of charge neutralizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
80
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(104 citation statements)
references
References 88 publications
17
80
1
Order By: Relevance
“…In Fig. 5(a), we compare the ζ-potential at various concentrations between our EOF simulations, the SC experiments of van der Lorenz et al, 26 our results for the different f -values and the simulation data from Biriukov et al 36 are in reasonable agreement with the experimental results from van der Heyden et al 9 and Rashwan et al 60 Notably, there is a considerable difference between ζ-potentials found by van der Heyden et al 9 and Rashwan et al 60 at 100 mmol/l. Comparable differences are found between values obtained from different electrokinetic techniques.…”
Section: ζ-Potentialsupporting
confidence: 77%
See 1 more Smart Citation
“…In Fig. 5(a), we compare the ζ-potential at various concentrations between our EOF simulations, the SC experiments of van der Lorenz et al, 26 our results for the different f -values and the simulation data from Biriukov et al 36 are in reasonable agreement with the experimental results from van der Heyden et al 9 and Rashwan et al 60 Notably, there is a considerable difference between ζ-potentials found by van der Heyden et al 9 and Rashwan et al 60 at 100 mmol/l. Comparable differences are found between values obtained from different electrokinetic techniques.…”
Section: ζ-Potentialsupporting
confidence: 77%
“…Heyden et al9 and Rashwan et al,60 the Atomic Force Microscopy (AFM) experiments from Siretanu et al,8 and previous MD results from EOF and SC simulations from Lorenz et al26 and EOF simulations from Biriukov et al36 Compared to the results from…”
mentioning
confidence: 99%
“…The relatively sharp feature observed at ~3670 cm -1 provides additional support for the charge inversion at high YCl3 concentrations. The high-frequency band is located in a similar frequency range as that observed for the OH stretches of Si-OH, Al-OH, and Ca-OH at the aqueous interface with silica, [43,79] alumina, [80] and calcium fluoride, [81] respectively. Thereby, it is assigned to the OH stretch of an yttrium hydroxide cation (i.e.…”
Section: Targetting Interfacial Water Molecules To Detect the Charge Reversion Of The Surfacesupporting
confidence: 62%
“…[47][48][49] We therefore find experimental evidence for a significant change in interfacial structure with increasing surface coverage for some of the ions we surveyed, consistent with reports by others for mica:water [50][51][52][53] and silica:water [47][48][49]54 interfaces. Previous studies of divalent cations, specifically magnesium and calcium, by Gibbs and co-workers, 55,56 have shown that low concentrations of these salts (0.033mM) attenuate the vibrational sum frequency generation (SFG)-resonant water signal in comparison to NaCl at similar concentrations albeit at a higher pH than the conditions studied here. The resonant vibrational SFG experiments attributed these trends to displacement of the hydration layer above the silica surface by ions retaining their centrosymmetric hydration shell.…”
Section: B Estimated Trends Inmentioning
confidence: 59%